2021
DOI: 10.1051/mfreview/2021025
|View full text |Cite
|
Sign up to set email alerts
|

Comparative investigation of the influence of kaolin and dolomite on the properties of polyurethane foam

Abstract: This work investigates the influence of kaolin and dolomite on the properties of polyurethane foam. The selected fillers were pulverized and sieved to obtained < 90 μm that were used as reinforcements in the polyurethane matrix in a randomly dispersed mode. The matrix constituents were mixed in the same ratio while fillers were introduced via a one-shot system approach in predetermined proportions of 3–7 wt.%. The work was carried out to identify optimum fillers to be utilized in the production of polyureth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 18 publications
(19 reference statements)
1
0
0
Order By: Relevance
“…Strąkowska et al [ 15 ] obtained an improvement in flexural strength by introducing POSS-impregnated sugar beet pulp in the foam in the amount of less than 5 wt%. Similar results were also obtained using dolomite and kaolin at up to 3 wt% and plum stones at 1 and 2 wt% [ 22 , 78 ].…”
Section: Resultssupporting
confidence: 80%
“…Strąkowska et al [ 15 ] obtained an improvement in flexural strength by introducing POSS-impregnated sugar beet pulp in the foam in the amount of less than 5 wt%. Similar results were also obtained using dolomite and kaolin at up to 3 wt% and plum stones at 1 and 2 wt% [ 22 , 78 ].…”
Section: Resultssupporting
confidence: 80%
“…Increasing the quantity of Kevlar pulp above the threshold value leads to no significant improvement besides being an intercellular filler and increasing insulation. Similarly, Omotoyinbo et al [33] showed that adding dolomite and kaolin altered the absorption peaks and improved the hardness, flexural, and compressive strength of RPUF. Felspar addition to RPUF was also found to alter the absorption peaks with improved microstructure and hydrophobicity but negatively affected the rheological properties and the sulfonic acid groups [34].…”
Section: Introductionmentioning
confidence: 95%
“…The time-dependent rheological properties were measured as the reaction proceeded using a stopwatch. The two-step process is done according to the works of Zieleniewska et al [24], Omotoyinbo et al [33], and Omotoyinbo et al [34], and Nunes de Oliveira Júnior et al [45]. An open mold with dimensions 81 mm × 100 mm × 130 mm was used for this research.…”
Section: Preparation Of Rpuf Compositesmentioning
confidence: 99%
See 2 more Smart Citations